Implementasi Simple Linear Regression untuk Meramalkan Perkembangan Pelanggan PLN - Yayang Eluis Bali Mawartika; Hendra Di Kesuma (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2022)
The rate of population growth in Lubuklinggau City continues to increase every year, this is a factor in the increasing demand for electricity. The development of the number of PLN customers in Lubuklinggau City in 2017 was 90.606 customers, increasing to 120.809 customers in 2021. PLN must be able to predict the number of electricity customers in the future in order to provide electricity needs. One of the forecasting models that can be used to predict the development of the number of PLN electricity customers is the Simple Linear Regression model. Simple Linear Regression is a forecasting model based on the effect of the causal variables on the effect variables. The variables used are the population variable and the number of PLN customers. From these two variables, the process of analyzing the influence of population on the number of PLN customers in the future will be carried out. The results showed that 90% increase in population affects the number of PLN customers. With the prediction of the development of the number of customers, PLN Lubuklinggau can prepare the necessary facilities and can estimate how much additional power and electrical energy will be in meeting customer needs in the future.